Prevention method of toric intraocular lens rotation after phacoemulsification of cataract using a standard capsule ring - Zavgorodnyaya, N. G.; Novikova, V. Yu.; Завгородня, Наталія Григорівна (My University, 2021)
At the same time, phacoemulsification of cataracts remains the most popular surgery. But the problem among phacosurgeons is the correction of existing corneal astigmatism. According to studies, about 30% of the world's population have corneal astigmatism with a strength of 0.75D and above, which leads to a decrease in visual acuity after phacoemulsification of cataracts in the absence of its correction.The most commonly used method to correct corneal astigmatism is the implantation of toric intraocular lenses (TIOL). The main condition for obtaining high visual acuity after TIOL implantation is the location of the astigmatic component of the artificial lens in accordance with the strong meridian of the cornea. The aimof this study wasto evaluate the effectiveness of the proposed method of preventingthe toric intraocular lens rotation after phacoemulsification of cataracts in the eyes with corneal astigmatism by implantation of a standart capsule ring.
Keywords: cataract; corneal astigmatism correction; cataract phacoemulsification; toric IOL